1983
DOI: 10.1021/ac00263a019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silica-immobilized 8-quinolinol with (aminophenyl)trimethoxysilane

Abstract: A more efflcleint and tlme-savlng synthetic route to sllicalmmoblllzed 8-quinolinol has been developed that results In a product exhibltlng a relatively large exchange capacity. A comparison of dlfferent sllica supports has been performed and the resulting slllca-bound 8-qulnolinol materlals have been characterized with regard to exchange capaclty, carbon content, acid-base properties, and stablllty. The dependence of capaclty on surface area and pore size Is dlscussed and a comparison i o conventionally prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 25 publications
2
65
0
1
Order By: Relevance
“…In this work, the feasibility of this procedure was demonstrated by immobilising 8-HQ onto CPG; however, it will be more appropriate for the attachment of oxines and similar reagents to silica surfaces within the porous structure of silica based monolithic materials (Asuhaimi, 2007). Moreover, it is green chemistry compatible, since no hazardous chemicals are used; therefore no harmful wastes are generated (Marshall and Mottola, 1983).…”
Section: Immobilisation Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the feasibility of this procedure was demonstrated by immobilising 8-HQ onto CPG; however, it will be more appropriate for the attachment of oxines and similar reagents to silica surfaces within the porous structure of silica based monolithic materials (Asuhaimi, 2007). Moreover, it is green chemistry compatible, since no hazardous chemicals are used; therefore no harmful wastes are generated (Marshall and Mottola, 1983).…”
Section: Immobilisation Reactionmentioning
confidence: 99%
“…For instance, during the benzoylation step, the substrate is heated for several hours in chloroform. Marshall and Mottola (Marshall and Mottola 1983) have used an aminophenyl silane '(aminophenyl)triethoxysilane' to activate the silica surface, which is then diazotised to facilitate oxine coupling in one step, thus significantly simplifed and shortened the immobilisation procedure; however, steric hindrance effect is more likely to distress resin functionality as the short linkage is not sufficient to distant the functional group away from the solid support.…”
mentioning
confidence: 99%
“…Therefore, 0, 5, 10, 20, and 40 ml additions of NH 4 OH (pH 7.3, 10.8, 11.1, and 11.6) were used. Figure 3 shows the effects of NH 4 OH on surface area, pore size, and pore volume. As the concentration of NH 4 OH increased (0-10 ml added NH 4 OH), surface area, pore size, and pore volume increased.…”
Section: Surface Area Pore Volume and Pore Sizementioning
confidence: 99%
“…[59][60][61][62] Some other modified silica gel with various kinds of complex-forming functional groups have been prepared and studied for their adsorption behavior and application to preconcentration of trace metals.63-65 Seshadri et a1.64 reported that a f3-diketone-immobiliz ed silica gel shows complexing affinity for Cu(II), U(VI; and Fe(III); no significant affinity is observed for Ni Co, Zn, Mg, Ca, La and Th. Furthermore, 2,3 f dihydroxybenzoyl and 3,4,5-trihydroxybenzoyl-amid functional groups immobilized silica exhibited signifi cant affinity for Cu, U, Fe, Ce, Ti, V, Mo and Cr.…”
Section: Poly(chlorotrifluoroethylene) Resins (Pctfe)mentioning
confidence: 99%